Performance Improvement of GaN-Based Vertical-Cavity Surface-Emitting Lasers by Using Tapered SiO2-Buried Structure - Rongbin Xu; Yachao Wang; Mingchao Fang; Yang Mei; Leiying Ying; Daquan Yu; Baoping Zhang (IEEE Photonics Journal, 2025)
In GaN-based vertical-cavity surface-emitting lasers (VCSELs) with insulator-buried structure, the strong index guiding will introduce higher order modes. In this paper, we present a novel GaN-based VCSEL with a tapered SiO2-buried structure by numerical simulations. Compared to conventional flat aperture VCSELs, tapered aperture VCSELs show the lower threshold current and higher slope efficiency, and can be attributed to the improvement of current distribution within the current injection aperture. Moreover, by adjusting the taper length, the current distribution in current injection aperture can be further changed, enabling single fundamental mode lasing. Additionally, the modulation bandwidth for tapered aperture VCSELs will also increase due to the reduction of parasitic capacitance. This research guides the development of high performance GaN VCSELs capable of achieving single transverse mode and high modulation rates for visible optical communication links and networks.